MEDI6012: Recombinant Human Lecithin Cholesterol Acyltransferase, High‐Density Lipoprotein, and Low‐Density Lipoprotein Receptor–Mediated Reverse Cholesterol Transport - Richard T. George; Liron Abuhatzira; Susan M. Stoughton; Sotirios K. Karathanasis; Dewei She; ChaoYu Jin; Nicholas A. P. S. Buss; Rebecca Bakker‐Arkema; Emily L. Ongstad; Michael Koren; Boaz Hirshberg (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background MEDI6012 is recombinant human lecithin cholesterol acyltransferase, the rate‐limiting enzyme in reverse cholesterol transport. Infusions of lecithin cholesterol acyltransferase have the potential to enhance reverse cholesterol transport and benefit patients with coronary heart disease. The purpose of this study was to test the safety, pharmacokinetic, and pharmacodynamic profile of MEDI6012. Methods and Results This phase 2a double‐blind study randomized 48 subjects with stable coronary heart disease on a statin to a single dose of MEDI6012 or placebo (6:2) (NCT02601560) with ascending doses administered intravenously (24, 80, 240, and 800 mg) and subcutaneously (80 and 600 mg). MEDI6012 demonstrated rates of treatment‐emergent adverse events that were similar to those of placebo. Dose‐dependent increases in high‐density lipoprotein cholesterol were observed with area under the concentration‐time curves from 0 to 96 hours of 728, 1640, 3035, and 5318 should be: mg·h/mL in the intravenous dose groups and 422 and 2845 mg·h/mL in the subcutaneous dose groups. Peak mean high‐density lipoprotein cholesterol percent change was 31.4%, 71.4%, 125%, and 177.8% in the intravenous dose groups and 18.3% and 111.2% in the subcutaneous dose groups, and was accompanied by increases in endogenous apoA1 (apolipoprotein A1) and non‐ATP‐binding cassette transporter A1 cholesterol efflux capacity. Decreases in apoB (apolipoprotein B) were observed across all dose levels and decreases in atherogenic small low‐density lipoprotein particles by 41%, 88%, and 79% at the 80‐, 240‐, and 800‐mg IV doses, respectively. Conclusions MEDI6012 demonstrated an acceptable safety profile and increased high‐density lipoprotein cholesterol, endogenous apoA1, and non‐ATP‐binding cassette transporter A1 cholesterol efflux capacity while reducing the number of atherogenic low‐density lipoprotein particles. These findings are supportive of enhanced reverse cholesterol transport and a functional high‐density lipoprotein phenotype. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02601560.